Vocabulary Materials Based on Picture Media for Autistic Students - Riryn Fatmawaty; Riya Risqi Setyaningrum; Fita Faridah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to develop image-based vocabulary material for autistic students at MTs Sunan Drajat Sugio Lamongan. This research is a Research and Development (R&D) research. The subjects of this study were autistic students at MTs Sunan Drajat Sugio Lamongan. Researchers used three instruments to obtain data, namely interviews, questionnaires and observation checklists. The results showed that autistic students needed vocabulary material that contained many exciting pictures, varied activities, and attractive colors. The product of this research is vocabulary material entitled Picture Vocabulary Mastery for Autistic Students, which is suitable for the needs of autistic students. In conclusion, autistic students like vocabulary material and these products can help autistic students learn English, especially vocabulary. Keywords: Autistic Students, Picture Media, Vocabulary